Is homework the solution to low academic performance? - Marcenaro-Gutiérrez, Óscar David; Jerrim, John; López-Agudo, Luis Alejandro (My University, 2018)
Parental associations have long held the view that Spanish elementary school pupils spend too much time undertaking homework. This situation is so alarming that it has recently (2016) caused a ‘homework strike’, which has been supported by many children’s parents. In light of this context, this paper aims to provide new evidence on the relationship between homework and academic performance in Spain. Using rich longitudinal data, and applying sibling (twin) fixed effects approach, we find that homework has essentially no impact upon young people’s academic achievement (at least within this specific country context).
Keywords: Escolares - Rendimiento; Homework; Compulsory education; Twins